Europe in America's Imagination (Czech Journal of International Relations, 1967)
In recent years, more and more books have been published in the capitalist world on the issue of world socialism and on the Western policy of socialist countries.Among the large number of authors, one of the most frequently published is the American theoretician Professor Zb. Brzezinskl. He is the author of several books on the problems of socialist countries, the Director of the Research Institute on Communist Affatrs at Columbia University in New York and, since mid-1966, a member of the State Department's planning group for European socialist countries. This review pointed to the important fact that the anti-scientific atmosphere of the time was opened in the USAof McCarthyism was replaced by a period of using leaders for political needs.Professor Brzezinski is the best proof of this and the currency of his work is current evidence of a significant increase in the role of ideological activity in the US in recent times, when the search for "new ideas!" which could influence the masses.